Geological effects influence population genetic connectivity more than Pleistocene glaciations in the water strider Metrocoris sichuanensis (Insecta: Hemiptera: Gerridae). (7th January 2018) - Ye, Zhen; Yuan, Juanjuan; Li, Min; Damgaard, Jakob; Chen, Pingping; Zheng, Chenguang; Yu, Haibin; Fu, Siying; Bu, Wenjun
Abstract: Aim: Palaeoclimatic and palaeogeological events have been identified as two main factors that influence the genetic structuring of extant organisms. We studied a montane stream‐dwelling insect, Metrocoris sichuanensis, to explore the relative roles played by these two factors in population genetic connectivity. Location: Sichuan Basin, China. Methods: Mitochondrial (COI, COII, Cytb, 16S) and nuclear (EF‐1α, ITS1) markers were sequenced from 208 individuals. Suitable habitat shifts from the Last Glacial Maximum (LGM) to the present were predicted through fine‐tuned ecological niche modelling (ENM). Phylogenetic and phylogeographical analyses were conducted to reveal the population genetic structure. Intraspecific divergence and expansion times were estimated usingbeast . Finally, the least cost path (LCP) method coupled with migrate analysis was used to identify possible dispersal corridors and estimate the asymmetric gene flow. Results: Our ENM results suggested that population habitat connectivity did not change both in the LGM and current conditions. Whole haplotypes were separated into four highly supported clades/haplogroups that exhibited strong geographical structure. The splitting events between the four lineages likely date back to the Early Pleistocene. Bayesian skyline plot (BSP) indicated a moderate demographic growth from the LGM to the present. A putative dispersal corridor was detected along the Longmen Mountains thrust belt, with unidirectional gene flow from north to south. Main conclusion: Our findings support the geographical isolation of the genetic lineages and a deep early Pleistocene split in M. sichuanensis . Landscape connectivity analysis incorporating the genetic data and the ENM prediction revealed that population genetic connectivity was strongly associated with stable climatic habitats shaped by complex topography. The drainage system might have assisted the rapid movement of populations along the Longmen Mountains thrust belt. A strategy for researching the population genetic connectivity of narrow endemics, such as M. sichuanensis, in global biodiversity hotspots is proposed and discussed in this paper.